2017
DOI: 10.1186/s40104-017-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral leukocyte and endometrium molecular biomarkers of inflammation and oxidative stress are altered in peripartal dairy cows supplemented with Zn, Mn, and Cu from amino acid complexes and Co from Co glucoheptonate

Abstract: BackgroundImmune dysfunction and a higher risk of uterine infections are characteristics of the transition into lactation in dairy cows. The supply of complexed trace minerals, which are more bioavailable, could help overcome the greater needs of these nutrients in tissues around parturition and early lactation.ResultsTwenty Holstein cows received an oral bolus with a mix of inorganic trace minerals (INO) or complexed trace minerals (AAC) to achieve 75, 65, 11, and 1 ppm supplemental Zn, Mn, Cu, and Co, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
2
14
0
1
Order By: Relevance
“…The down regulation of cell structure and cell adhesion pathways was also observed from both proteomics [22] and the present RNA sequencing results. When compared to other studies made in the cow [20, 21, 29, 41], human [30] and mouse [42] endometrium, our results fully confirm that a high number of differentially expressed genes relates to immune response, response to infection and inflammation and also to cell metabolism and oxidative stress [22, 43]. Former studies in the cow, reported changes in genes involved in embryo maternal interaction, notably interferon (IFN)-stimulated genes RSAD2 , MX2 , OAS1 , ISG15 , BST2; as well as several molecules involved in the intracellular recognition of pathogens or their ligands, including IFIH1 , MDA5 , DEXH Asp-Glu-X-His box polypeptide 58 (DHX58) , and up-regulation of a large number of chemokines such as IL8 , CCL4 , CCL20 , CXCL2 , CXCL3 , CSCL10 , CXCL11 , CCL3 , CCL4 , CCL11 , and CCL20 .…”
Section: Discussionsupporting
confidence: 85%
“…The down regulation of cell structure and cell adhesion pathways was also observed from both proteomics [22] and the present RNA sequencing results. When compared to other studies made in the cow [20, 21, 29, 41], human [30] and mouse [42] endometrium, our results fully confirm that a high number of differentially expressed genes relates to immune response, response to infection and inflammation and also to cell metabolism and oxidative stress [22, 43]. Former studies in the cow, reported changes in genes involved in embryo maternal interaction, notably interferon (IFN)-stimulated genes RSAD2 , MX2 , OAS1 , ISG15 , BST2; as well as several molecules involved in the intracellular recognition of pathogens or their ligands, including IFIH1 , MDA5 , DEXH Asp-Glu-X-His box polypeptide 58 (DHX58) , and up-regulation of a large number of chemokines such as IL8 , CCL4 , CCL20 , CXCL2 , CXCL3 , CSCL10 , CXCL11 , CCL3 , CCL4 , CCL11 , and CCL20 .…”
Section: Discussionsupporting
confidence: 85%
“…S100A8/9 is known to regulate NADPH oxidase activity, which is the major source of ROS in neutrophil. Similar changes also occurred during the periparturient period that ROS production by PMN stimulated with PMA decreased prominently and reached the lowest level at calving (28,29), although the expression of S100A8/9 had increased compared to the prepartum (8,30); thus, we postulate that the decrease in PMA-induced ROS production was likely caused by OF overload, which results in increased production of ROS in vivo, yet exhausted PMN was unable to produce more additional ROS in response to the PMA stimulation. SOD can catalyze the dismutation of superoxide into hydrogen peroxide, which is reduced to water by catalase (27).…”
Section: Discussionmentioning
confidence: 52%
“…The lack of overall effect of RFI on DMI between wk − 4 to 3 relative to calving or on FCM during the first 60 DIM suggests that RFI per se was not associated with measures of performance during a period when energy and protein balance are at a nadir. It could be possible that the metabolic and immune challenges cows experience during the peripartal period [ 9 , 32 ] exert some level of control on DMI in the least-efficient cows while the most-efficient cows are able to maintain or decrease DMI within a narrow margin such that marked differences among groups are difficult to detect statistically. The fact that the most-efficient compared with least-efficient cows consumed on average 2.6 kg DMI/d less by wk 4 postpartum indicates that once “stressors” (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The “peripartal” period in dairy cows is characterized by a marked negative energy and metabolizable protein balance at least in part due to the decrease in voluntary DMI and the high requirements for nutrients by the fetus and lactating mammary gland. Therefore, the peripartal period is challenging for dairy cows resulting in higher susceptibility for developing metabolic disorders [ 9 11 ]. Current nutritional management of peripartal cows encompasses the feeding of higher-concentrate diets postcalving to provide the rumen bacterial communities with a more readily-available source of energy.…”
Section: Introductionmentioning
confidence: 99%